Market Dynamics at Play: The Convergence Phenomenon in Carbon Credit Project Valuations - Bereczk, Ádám; Musinszki, Zoltán; Hlad, Edina (Észak-magyarországi Stratégiai Füzetek, 2024)
This study examines the capital market valuation of carbon trading projects in the growth stage, focusing on the impact of project size and classification. We analyze four projects launched in 2021 and 2022, using changes in market capitalization as a proxy for valuation, based on investor perception. A major conclusion of the paper is that the market capitalization of different projects converged over the study period. This phenomenon was evident despite the differences in the amount of capital raised, launching market caps, size of partner networks and timing of launching. We argue that the novelty of the sector fosters investor focus on sectoral narratives, leading to converging project valuations. This convergence in market capitalization should be factored into tokenomics design and market-making activities to ensure the financial sustainability of these blockchain projects.